Modeling precipitation thermodynamics and kinetics in type 316 austenitic stainless steels with varying composition as an initial step toward predicting phase stability during irradiation - Shim, Jae-Hyeok; Povoden-Karadeniz, Erwin; Kozeschnik, Ernst; Wirth, Brian D. (ELSEVIER SCIENCE BV, 2015)
The long-term evolution of precipitates in type 316 austenitic stainless steels at 400 degrees C has been simulated using a numerical model based on classical nucleation theory and the thermodynamic extremum principle. Particular attention has been paid to the precipitation of radiation-induced phases such as gamma' and G phases. In addition to the original compositions, the compositions for radiation-induced segregation at a dose level of 5, 10 or 20 dpa have been used in the simulation. In a 316 austenitic stainless steel, gamma' appears as the main precipitate with a small amount of G phase forming at 10 and 20 dpa. On the other hand, G phase becomes relatively dominant over gamma' at the same dose levels in a Ti-stabilized 316 austenitic stainless steel, which tends to suppress the formation of gamma'. Among the segregated alloying elements, the concentration of Si seems to be the most critical for the formation of radiation-induced phases. An increase in dislocation density as well as increased diffusivity of Mn and Si significantly enhances the precipitation kinetics of the radiation-induced phases within this model. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: RADIATION-INDUCED SEGREGATION; GRAIN-BOUNDARY SEGREGATION; STRESS-CORROSION CRACKING; MULTICOMPONENT MULTIPHASE SYSTEMS; ATOM-PROBE TOMOGRAPHY; MICROSTRUCTURAL EVOLUTION; CR DEPLETION; ALLOYS; 304-STAINLESS-STEEL; BEHAVIOR